Rate Acceleration of Baylis-Hillman Reaction with Lithium Bromide and 1,8- Diazabicyclo[5.4.0]undec-7-enein Solvent Free Medium - Mamaghani, Manouchehr; Radmogadam, Korosh; Badrian, Abed (Asian Journal of Chemistry, 2010)
The Baylis-Hillman reaction was accelerated in the presence of catalytic amount of lithium bromide and 1,8-diazabicyclo[5.4.0]undec-7-ene in a solvent free medium. A preliminary kinetic study revealed that the relative rate of the reaction using lithium bromide was considerably faster than that of reaction without lithium bromide.